Morphology of SiO2 films as a key factor in alignment of liquid crystals with negative dielectric anisotropy - Volodymyr Tkachenko; Antigone Marino; Eva Otón; Noureddine Bennis; Josè Manuel Otón (Beilstein Journal of Nanotechnology, 2016)
Control of liquid crystal (LC) orientation using a proper SiO2 alignment layer is essential for the optimization of vertically aligned nematic (VAN) displays. With this aim, we studied the optical anisotropy of thin SiO2 films by generalized ellipsometry as a function of deposition angle. The columnar SiO2 structure orientation measured by a noninvasive ellipsometry technique is reported for the first time, and its morphology influence on the LC alignment is demonstrated for large deposition angles.